Matematika untuk Anak (Penalaran dan Bimbingan Permainan) - Maragustam Maragustam (Mukaddimah: Jurnal Studi Islam, 2018)
Mathematic make easier daily human activities for example : an economic activities, politic, culture, health, etc so that needs to be taught since early. But, based on the result of researcher supervision, a mathematic learning method in Early Children Education Institution (PAUD), there is an institution which has not used yet guidance, reasoning, and game. This thing is not suitable with characteristic and learning principle of early children. This condition form the background of this research. This research aims to develop the mathematic learning method of early children by using guidance, reasoning, and games. Developing result is a product for mathematic learning of early children in PAUD Institution. The product is manipulative objects which consist of concrete object game, semi concrete object games, mathematic object games. The test result shows that product which is developed has fulfilled a valid criteria that is shown by validation averages result by two validator, complete practical criteria that is shown by user evaluation result and complete an effective criteria that is shown by the test result averages of children evaluation.